Performance analysis of the Nb−Ti conductor qualification samples for the ITER project. (15th September 2015) - Breschi, M; Carati, D; Bessette, D; Devred, A; Romano, G; Vostner, A; Zhou, C
Abstract: The ITER machine will require approximately 275 tons of Nb−Ti strands that will be used in poloidal field (PF) coils, correction coils (CC) and feeder busbars. The performance of all these conductors for the ITER machine is qualified by a short full-size sample (4 m) current sharing temperature ( T cs ) test in the SULTAN facility at CRPP in Villigen, Switzerland, at the design operating current and peak field. Three ITER domestic agencies participated in PF conductor fabrication (China, the European Union, Russia) while the conductors for feeder busbars and correction coils are entirely produced by the Chinese domestic agency. Each conductor type was qualified by the ITER International Organization after reaching T cs values in excess of ITER specifications. This qualification enabled the launch of procurement and industrial production of the Nb−Ti cable-in-conduit conductors in each domestic agency. In this paper, we summarize the performance of the qualified Nb−Ti samples of the ITER Project, comparing strand performance with conductor performance. The details of the test results will be discussed in terms of dc performance, ac losses and minimum quench energies of each conductor type.